An Epidemiological Profile of the Laboratory Confirmed COVID-19 Cases Reported in Baluchistan Province - Khan, Jahanzaib; Saeed, Abid; Ahmad, Farah (Infectious Diseases Journal of Pakistan, 2022)
Introduction: The novel Corona virus disease 2019 (COVID 19) is an emerging respiratory tract disease caused by a corona virus’s family virus, SARS COV-2 virus. This illness emerged from China during December 2019. Now it has spread to whole world becoming a pandemic. Pakistan is also affected with COVID-19 and bordered with countries, which were highly affected by COVID19. It entered Baluchistan province with the of return of Pilgrims from Iran through Pak-Iran border. Methods: A (Cross-sectional) study was conducted in Baluchistan province in the second quarter of 2020. In this study, the epidemiological analysis of the laboratory positive cases was conducted including the deaths reported. The data was collected on using standard case investigation form for COVID-19, analyzed in SPSS-22, and Microsoft excel. Descriptive analysis was done and data was presented in form of mean, attack rates, frequency tables, graphs, and figures. Results: Total 45016 individuals were screened in Baluchistan province in the second quarter of 2020, and 41% (n=18627) were found suspected based on case definition used. PCR for COVID-19 was done for 91% (n= 16884) among suspected cases and 15% (n=2544) resulted COVID-19 positive. The overall attack rate calculated was 25.41/100000 population. Recovery rate among COVID-19 positive cases was 16.3% (n=417) and deaths reported were 2.2 % (n=36). Majority 77.8 % (n=1980) of positive cases were Males. The mean age was 34.9 years with age range 0 - 94 years. Total 66 % (n=22) districts were infected, among these 84.75% (n=2156) cases were from district Quetta with an attack rate of 88.66%. Total 36 deaths reported among the laboratory positive COVID 19 Cases during study period. The overall mortality rate was 2.33% with Male gender predominance 83 % (n=30) mostly 86 %( n=31) among age group above 45 years. Conclusion and recommendations: Immediate measures like lockdown in province and closure of borders were implemented to cease transmission of virus. The incoming pilgrims were quarantined at the borders in quarantine centers, screened, and tested for COVID-19. We recommended governance, policy formulation, enhanced operational capability, capacity building of the Health workforce, awareness among community to follow the lockdowns, social distancing, and other preventive measures against this novel corona virus disease. Keywords: COVID-19, SARS-COV 2, Baluchistan, Pak Iran Border, Zaireen (Pilgrims)